2021
DOI: 10.1038/s41416-020-01253-1
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in oral and gut microbiome of HPV+ oropharyngeal squamous cell carcinoma following definitive chemoradiotherapy (ROMA LA-OPSCC study)

Abstract: Background Oral and gut microbiomes have emerged as potential biomarkers in cancer. We characterised the oral and gut microbiomes in a prospective observational cohort of HPV+ oropharyngeal squamous cell carcinoma (OPSCC) patients and evaluated the impact of chemoradiotherapy (CRT). Methods Saliva, oropharyngeal swabs over the tumour site and stool were collected at baseline and post-CRT. 16S RNA and shotgun metagenomic sequencing were used to generate tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…An increased number and diversity of fungi, in addition to Candida , have been detected (e.g., Peniophora, Stereum, Cladosporium ) ( 3 ). The total number of bacteria tends to decrease immediately after treatment and gradually return, while the relative abundance of certain species (e.g., Streptococcus mutans ) and genera (e.g., Bifidobacterium, Lactobacillus) tend to increase and reflect gut-associated obligate anaerobes ( 3 , 27 , 28 , 33 , 35 ). Regarding archea, there seems to be little to no change due to RT ( 3 ).…”
Section: Radiation Therapy and Changes In The Head And Neck Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…An increased number and diversity of fungi, in addition to Candida , have been detected (e.g., Peniophora, Stereum, Cladosporium ) ( 3 ). The total number of bacteria tends to decrease immediately after treatment and gradually return, while the relative abundance of certain species (e.g., Streptococcus mutans ) and genera (e.g., Bifidobacterium, Lactobacillus) tend to increase and reflect gut-associated obligate anaerobes ( 3 , 27 , 28 , 33 , 35 ). Regarding archea, there seems to be little to no change due to RT ( 3 ).…”
Section: Radiation Therapy and Changes In The Head And Neck Microbiomementioning
confidence: 99%
“…The studies we present have methodological advantages over culture-based techniques: superior sensitivity, specificity, and speed in detecting microorganisms that may be responsible for causing RT-induced toxicity ( 39 , 66 ). By using “sequencing by synthesis” methods that target the 16S rRNA subunit ( 67 ), studies in this review allow for identification of microorganisms at the phyla and genera levels, while one study ( 33 ) used metagenomic shotgun sequencing to capture species-level changes. Recent advancements in molecular processing have made possible the use of a multi-omic approach—metagenomics, metabolomics, metatranscriptomics, and metaproteomics ( 68 )—to identify strain-level microorganisms and obtain additional information on how the microbiome may be related to clinical changes in the host ( 27 , 69 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…This study was positively classified in our LitSuggest analysis ( Table 3 ). A study by Oliva et al (2021) found that Leptotrichia hofstadii was abundant in stage III oropharynx cancer, while Zakrzewski et al (2021) determined Leptotrichia genus to be decreased in oropharynx HPV- tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal swabs and stool samples were collected from a cohort of patients with human papillomavirus-positive (HPV + ) locoregionally advanced oropharyngeal squamous cell carcinoma (LA-OPSCC) treated with chemoradiotherapy (CRT) ( 13 ). Oropharyngeal swabs over the tumor site and stool samples were collected up to 3 weeks prior to the start of radiotherapy and again at completion of CRT (up to 3 weeks following last day of radiotherapy) ( 13 ). Oropharyngeal swabs over the tumor site and stool samples were collected using the ZymoBIOMICS DNA/RNA mini prep kits (Zymo Research, Irvine, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Oropharyngeal swabs over the tumor site and stool samples were collected using the ZymoBIOMICS DNA/RNA mini prep kits (Zymo Research, Irvine, CA). DNA was extracted using ZymoBIOMICS DNA micro kit ( 13 ).…”
Section: Methodsmentioning
confidence: 99%